2022
DOI: 10.1101/2022.03.04.482796
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human NMDAR autoantibodies disrupt excitatory-inhibitory balance leading to hippocampal network hypersynchrony

Abstract: Specific autoantibodies against the NMDA-receptor (NMDAR) GluN1 subunit cause severe and debilitating NMDAR-encephalitis. Autoantibodies induce prototypic disease symptoms resembling schizophrenia, including psychosis and cognitive dysfunction. Using a mouse passive transfer model applying human monoclonal anti-GluN1-autoantibodies, we observed CA1 pyramidal neuron hypoexcitability, reduced AMPA-receptor (AMPAR) signaling, and faster synaptic inhibition resulting in disrupted excitatory-inhibitory balance. Fun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 93 publications
(143 reference statements)
0
7
0
Order By: Relevance
“…The animal model can now be used for additional investigations on the role of NMDAR in memory maintenance and recall as well as for novel approaches (i.e., allosteric modulators of NMDA or AMPA receptors) to treat the long-term memory and behavioral alterations of the disease. 24,52…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The animal model can now be used for additional investigations on the role of NMDAR in memory maintenance and recall as well as for novel approaches (i.e., allosteric modulators of NMDA or AMPA receptors) to treat the long-term memory and behavioral alterations of the disease. 24,52…”
Section: Discussionmentioning
confidence: 99%
“…With a computational model, they showed that the transition to an ictogenesis was best explained by changes in synaptic weights that pushed excitation/inhibition out of balance. Ceanga et al 52 used in-vitro recordings and a computational model to demonstrate that changes in excitation/inhibition balance caused by lower AMPAR strength and faster GABAA-receptor kinetics, mainly accounted for the abnormal EEG oscillations. Therefore, we provide here a different set of studies focused on memory and behavior, in which we were able to link the excitation/inhibition unbalance with alterations of these tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Curve permutation tests were performed by comparing the difference in the area under the curve of the group-averaged curves, with those obtained after shuffling the individual curves across groups, with 1 million times repetition; see Ref. 35 for more details. To statistically compare the cluster density and distance parameters between groups at proximal, middle, and distal sections, we adapted the permutation test of Cohen, thereby accounting for multiple comparison problem.…”
Section: Methodsmentioning
confidence: 99%
“…Using a passive transfer mouse model, the antibodies caused disrupted excitatory-inhibitory balance resulting in hippocampal CA1 neuronal hypoexcitability, reduced AMPAR signaling, and faster synaptic inhibition in acute hippocampal slices, ultimately triggering increased gamma oscillations. A positive allosteric modulator of AMPAR improved the aberrant gamma activity, suggesting a potentially novel treatment [111 ▪▪ ]. Another observation suggested that pregnenolone, a neurosteroid that upregulates NMDAR, reduced epileptic activity in brain slices from a rat passive transfer model [112].…”
Section: Antibody-mediated Mechanisms In Nmdar Encephalitismentioning
confidence: 99%
“…The effects of patients’ antibodies not only induce functional and structural synaptic changes at the cellular level, but also produce important changes at the circuitry level [111 ▪▪ ,112]. Using a passive transfer mouse model, the antibodies caused disrupted excitatory-inhibitory balance resulting in hippocampal CA1 neuronal hypoexcitability, reduced AMPAR signaling, and faster synaptic inhibition in acute hippocampal slices, ultimately triggering increased gamma oscillations.…”
Section: Antibody-mediated Mechanisms In Nmdar Encephalitismentioning
confidence: 99%